2016
DOI: 10.3758/s13423-016-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

Red vs. green: Does the exam booklet color matter in higher education summative evaluations? Not likely

Abstract: We examined the so-called "red effect" in the context of higher education summative exams under the premise that unlike the conditions or situations where this effect typically has been obtained, the totality of factors, such as higher motivation, familiarity with exam material, and more reliance on domain knowledge that characterize high-stakes testing such as those in operational educational settings, are likely to mitigate any color effects. Using three naturally occurring archival data sets in which studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There are several reasons why an examination of the effect of colour of test in a booklet on exam performance in higher education summative evaluation is important. Colour stimuli may vary on lightness, hue and chromatography (Arthur, Cho and muñoz, 2016). In present study, most of the students i.e.,86% show increase in grades.…”
Section: Resultsmentioning
confidence: 86%
“…There are several reasons why an examination of the effect of colour of test in a booklet on exam performance in higher education summative evaluation is important. Colour stimuli may vary on lightness, hue and chromatography (Arthur, Cho and muñoz, 2016). In present study, most of the students i.e.,86% show increase in grades.…”
Section: Resultsmentioning
confidence: 86%
“…The pattern of findings obtained was not clear-cut: Some studies have found that red (vs. blue or green) inhibits performance, whereas others show that it facilitates it (for a review, see Mehta & Zhu, 2009). Other studies did not observe any differences produced by color in performance (Arthur, Cho, & Muñoz, 2016;Larsson & von Stumm, 2015).…”
Section: The Meanings and Effects Of Red And Green (And Blue)mentioning
confidence: 74%
“…As mentioned already, the particular context, the salience of the red stimulus, the uncertainty or ambiguity in the decision, and numerous other factors may determine whether a red effect can be detected. A growing number of researchers have failed to find effects in various contexts ( Allen & Jones, 2012 ; Arthur, Cho, & Muñoz, 2016 ; García-Rubio et al, 2011 ; Hesslinger, Goldbach, & Carbon, 2015 ; Larsson & von Stumm, 2015 ; Lynn, Giebelhausen, Garcia, Li, & Patumanon, 2013 ; Pollet & Peperkoorn, 2013 ; Smajic, Merritt, Banister, & Blinebry, 2014 ; Steele, 2014 ). As such, the current results might be the result of difficulties in generalizing to real-world contexts or situations where a variety of influences are present.…”
Section: Discussionmentioning
confidence: 99%